Intravenous radionuclide therapy with radium chloride [223Ra] in patients with bone metastases from castration-resistant prostate cancer - O. I. Kit; N. A. Maksimova; M. A. Gusareva; A. N. Shevchenko; M. S. Zinkovich; M. G. Ilchenko; K. P. Boyko; A. V. Faenson; S. N. Dimitriadi; L. Ya. Rozenko (Южно-Российский онкологический журнал, 2024)
Purpose of the study. Assessment of clinical safety and effectiveness of radium‑223 in patients with bone metastases from castration-resistant prostate cancer.Patients and methods. The study involved materials on 15 patients with bone metastases from castration-resistant prostate cancer aged 58–81 years, with the mean age of 67.2 ± 6.5 years, who were examined and received full treatment with 6 intravenous injections of radium‑223 chloride [223Ra] at the National Medical Research Centre for Oncology. Most patients (73.3 %) showed ECOG 1 performance status. Pain syndrome before the treatment was registered in 12 (80 %) patients.Results. Evaluation of the tolerability of radium chloride did not show hematological reactions such as anemia and thrombocytopenia. One patient had grade II intestinal toxicity after the 3rd injection managed with medication. Assessment of indirect signs of the treatment effectiveness demonstrated that 6 people showed an increase in PSA during treatment, while alkaline phosphatase levels were within normal range indicating no bone destruction. 8 of 12 patients with pain syndrome showed its relief during the therapy. The following results were obtained during a follow-up examination after 3 months in 15 patients who received the full treatment course: stabilization in 8 patients; improvement in 4 patients with decreased metabolic activity and lower numbers of metastatic foci; progression with the appearance of new metastatic foci in the bones in 3 patients.Conclusion. Radium chloride showed good results in the treatment of patients with bone metastases from castration-resistant prostate cancer. Low toxicity and improvement in the quality of life by pain relief make this treatment technique promising.